2007
DOI: 10.1093/protein/gzm039
|View full text |Cite
|
Sign up to set email alerts
|

C-terminus engineering of soybean proglycinin: improvement of emulsifying properties

Abstract: Introduction of the extension region of beta-conglycinin alpha' subunit at the C-terminus of proglycinin A1aB1b results in the improvement of its emulsifying properties. To understand the basic for such improvement, we introduced the alpha' and alpha extension regions to the A2B1a C-terminus, and the alpha extension and A5A4B3 hypervariable regions, and an oligopeptide composed of 20 negatively or positively charged residues to the A1aB1b C-terminus, creating A2B1aalpha', A2B1aalpha, and A1aB1balpha, A1aB1bA4I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Many studies have revealed that a protein's emulsifying ability is actually dependent on the balance between the surface hydrophobicity and hydrophilicity (solubility or surface charge) (Prak, Nakatani, Maruyama, & Utsumi, 2007;Tang & Sun, 2010;Voutsinas, Cheung, & Nakai, 1983). The 11S proglobulins used in this study generally have similar surface hydrophobicity, as shown in Fig.…”
Section: Surface Character Emulsifying Property and Aggregation Tenmentioning
confidence: 79%
“…Many studies have revealed that a protein's emulsifying ability is actually dependent on the balance between the surface hydrophobicity and hydrophilicity (solubility or surface charge) (Prak, Nakatani, Maruyama, & Utsumi, 2007;Tang & Sun, 2010;Voutsinas, Cheung, & Nakai, 1983). The 11S proglobulins used in this study generally have similar surface hydrophobicity, as shown in Fig.…”
Section: Surface Character Emulsifying Property and Aggregation Tenmentioning
confidence: 79%
“…Proteins extracted from soybeans are essential ingredients for industrial food products such as beverages and nutraceuticals because they are affordable, with health benefits [1][2][3]. However, untreated soy proteins are not readily applicable because of limited surface-active properties (e.g., emulsifying property) and solubility.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of European and Japanese soybean-allergenic patients have IgE antibodies to glycinin and -conglycinin (Holzhauser et al, 2009;Ito et al, 2011). The structural analysis of these proteins is essential for the improvement of the nutritional qualities and functional properties of these proteins, as well as for elucidation of their allergenicity (Prak et al, 2006(Prak et al, , 2007Prak & Utsumi, 2009;Tandang et al, 2005). However, because of the heterogeneity of the molecular species, it is difficult to crystallize mature glycinin prepared from normal soybean cultivars (Utsumi, 1992).…”
Section: Introductionmentioning
confidence: 99%